Nutritional status of hospitalized elderly patients in Ethiopia: a cross-sectional study of an important yet neglected problem in clinical practice - Tesfaye, Behailu Terefe; Yizengaw, Mengist Awoke; Birhanu, Tesema Etefa; Bosho, Dula Dessalegn (Frontiers in Nutrition, 2024)
Background: Malnutrition is a common geriatric syndrome affecting about half of the older population with a more pronounced occurrence rate in those hospitalized. It affects the physiology, and results in poor humanistic and clinical outcomes. In Africa, particularly in Ethiopia, albeit multiple studies are available on malnutrition in non-hospitalized older population, similar studies in inpatient settings are scarce. Therefore, this study was conducted with the intention to quantify the prevalence of malnutrition in older patients on inpatient admission and determine its associated factors. Methods: A total of 157 older inpatients aged 60 and above years were included in the present study. Data collection format was developed after in-depth review of relevant literatures. The full Mini-nutritional assessment (MNA) tool was employed to assess the nutritional status on admission. Data completeness was checked thoroughly. Descriptive statistics and logistic regression analysis were conducted using STATA 15.0. The area under the receiver operating characteristic curve (ROC), Hosmer-Lemshow test, and classification table were performed to evaluate the final model goodness-of-fit. Results: Of the total study subjects, 81% were malnourished (MNA score <17) and 17% were at risk for malnutrition (MNA score of 17.5-23.5). However, upon review of patients` medical chart, malnutrition diagnosis was recorded in only two patients. Rural residence (AOR=2.823, 95%CI: 1.088, 7.324), self-reported financial dependence for expenses (AOR= 4.733, 95%CI: 1.011, 22.162), and partial dependence in functional autonomy on admission (AOR=3.689, 95%CI: 1.190, 11.433) significantly increased risk of malnutrition. The area under ROC curve (0.754) and the Hosmer-Lemshow test (p=0.7564) indicated that the final model reasonably fits the data. The model`s sensitivity is 96.85%. Conclusion: In the present study, alarmingly high prevalence of malnutrition was identified in almost all older inpatients. The problem went undiagnosed in similar percentage of patients. Several available literature indicates the presence of association between nutritional status and patient outcomes, thus strict nutritional screening at inpatient admission and intervention is recommended with special emphasis for those from rural area, with financial dependence, and with functional impairment on admission.